2010
DOI: 10.1007/s10800-010-0122-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical determination of thiamazole at a multi-wall carbon nanotube modified glassy carbon electrode

Abstract: A simple and convenient method is described for voltammetric determination of thiamazole, a commonly used anti-hyperthyroid drug, based on its electrochemical oxidation at a multi-wall carbon nanotube modified glassy carbon electrode. Under optimized conditions, the proposed method exhibited acceptable analytical performances in terms of linearity (over the concentration range from 1.0 9 10 -7 to 5.0 9 10 -4 mol L -1 , r = 0.9983), detection limit (3.0 9 10 -8 mol L -1 ) and reproducibility (RSD = 2.64%, n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Previous electrochemical research has demonstrated that thiamazole can be oxidized to form highly reductive radicals (Fig. 7, II) (15,26). The oxidation peak is~0.45 V, which is much lower than that of Ru(bpy) 3 2+ (~1.20 V) (27).…”
Section: +mentioning
confidence: 89%
“…Previous electrochemical research has demonstrated that thiamazole can be oxidized to form highly reductive radicals (Fig. 7, II) (15,26). The oxidation peak is~0.45 V, which is much lower than that of Ru(bpy) 3 2+ (~1.20 V) (27).…”
Section: +mentioning
confidence: 89%
“…The ECL reactions of these drugs in the presence of Ru(bpy) 3 2+ probably include a similar neutral radical mechanism. All of the four TDs studied are sulfhydryl compounds, they are easily oxidized to form highly reducing radicals (labeled as RS·) . The oxidation peak potentials on a Pt disk electrode are ∼+0.25, ∼+0.8, ∼+0.45, and ∼+0.5 V for TAP, TU, PTU, and MTU, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical methods, due to their advantages such as high sensitivity, high speed, and low-cost have been used in pharmaceutical analysis for a long time. Analysis of MMZ has been done by using modified electrodes such as glassy carbon electrode modified with multi-walled carbon nanotubes (Xi et al, 2010), an electrode modified with acetylene black/chitosan film (Yazhen, 2011), and a carbon paste electrode modified with a cobalt Schiff base complex (Shahrokhian and Ghalkhani, 2008).…”
Section: Methimazole Mmzmentioning
confidence: 99%